2022
DOI: 10.1101/2022.02.02.22269817
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LGE-MRI for diagnosis of left atrial cardiomyopathy as identified in high-definition endocardial voltage and conduction velocity mapping

Abstract: Background: Electro-anatomical voltage, conduction velocity (CV) mapping and late gadolinium enhancement magnetic resonance imaging (LGE-MRI) are different diagnostic modalities for atrial cardiomyopathy (ACM). However, discordances remain in the location and extent of detected ACM. Objectives: (1) Comparison of ACM extent and location between current modalities. (2) Development of new estimated optimised image intensity thresholds (EOIIT) for LGE-MRI identifying patients with ACM. Methods: Thirty-six ablation… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
(53 reference statements)
1
7
0
Order By: Relevance
“…The findings that different LGE-MRI evaluation methods disagree confirms previous reports, 4,5 which also showed that in comparison to LGE-MRI analysis, endocardial voltage and conduction velocity mapping yield different results, particularly on the posterior wall. Left atrial activation times as a functional readout of atrial substrate hardly correlated with any LGE-MRI derived metric (all nonsignificant) but with low voltage extent.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…The findings that different LGE-MRI evaluation methods disagree confirms previous reports, 4,5 which also showed that in comparison to LGE-MRI analysis, endocardial voltage and conduction velocity mapping yield different results, particularly on the posterior wall. Left atrial activation times as a functional readout of atrial substrate hardly correlated with any LGE-MRI derived metric (all nonsignificant) but with low voltage extent.…”
supporting
confidence: 88%
“…Left atrial activation times as a functional readout of atrial substrate hardly correlated with any LGE‐MRI derived metric (all nonsignificant) but with low voltage extent 4 . Both PIH and IIR methods were similarly sensitive (58%–60%) and specific (75%) for prediction of low voltage <0.5 mV in sinus rhythm in persistent AF patients 5 . Optimized methods derived from larger cohorts may increase the agreement between LGE‐MRI and voltage‐based substrate assessment 5 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…IIR or Utah) and the respective cut-off values are influencing the estimated fibrotic distribution. 8 , 10 Moreover, current LGE-MRI technology does not have the required resolution to well distinguish fibrosis within the thin atrial myocardial wall. Accuracy is essential in this case, as inclusion of external structures in the segmented myocardium can lead to a consideration of fat or outer tissue as scar or fibrosis, and omitting parts of the myocardium in the segmentation may hinder detection of fibrotic areas.…”
Section: Discussionmentioning
confidence: 99%
“…In a more recent study focused on a cohort of 37 ablation‐naïve patients, Eichenlaub et al 21 concluded that there were large discrepancies between the extent of LA fibrosis estimated by the IIR and PIH approaches, which is highly consistent with our own findings. Lastly, data presented in a preprint by Nairn et al 22 assess differences in LGE‐MRI delineation approaches in the context of intracardiac voltage mapping and characterization of left atrial conduction velocity. Their findings confirm that important discordances exist in the extent and spatial localization of identified pathological LA substrate depending on the LGE‐MRI segmentation method used.…”
Section: Discussionmentioning
confidence: 99%